Analisis Kemungkinan Penerapan Isak 335 dalam Penyajian Laporan Keuangan (Studi Kasus Pada Pondok Pesantren Nurul Yaqin Batipuah Ateh) - Dhia Wafi; Sri Adella Fitri; Resvina Aida; Salsa Nanda Maharani; Sefmaini Bilqis; Ulfa Fadila (Universitas Warmadewa, 2025)
This study aims to analyze the proposed implementation of ISAK 335 in the preparation of financial statements at Pondok Pesantren Nurul Yaqin Batipuh Ateh. As a form of nonprofit organization, Islamic boarding schools share characteristics with foundations, emphasizing social services and religious education rather than profit generation. The research findings indicate that the pesantren's operational funds are sourced from donors, the general public, and fundraising activities during Ramadan, which are allocated for infrastructure development and educational activities. However, the financial recording is still carried out manually by the pesantren’s treasurer and has not yet utilized a technology-based accounting system. Considering the importance of accountability and transparency in nonprofit organizations, the application of ISAK 335 is highly relevant for preparing standardized financial reports, enhancing public trust, and supporting future plans for external financial audits. The implementation of ISAK 335 is expected to assist Pondok Pesantren Nurul Yaqin in developing a more structured and accountable financial reporting system.